Robust Integrated Guidance and Control Design for Angle Penetration Attack of Multimissiles - Huan Zhou; Xin Zhao (International Journal of Aerospace Engineering)
Angle penetration attack ability plays a more and more important role for missiles in modern warfare, and the traditional separate guidance and control system design problem is the key to restrict the improvement of time-sensitive attack and cooperative attack ability of multimissiles. Firstly, the deviation control strategy of line-of-sight angle and attack angle is put forward in this paper, and the integrated guidance and control system model with impact angle constraint is established, according to the characteristics of angle penetration attack. Then, an integrated guidance and control controller for angle penetration attack is designed by using adaptive dynamic surface control, with the dynamic constraints, nonlinear input saturation, and terminal line-of-sight and attack angle constraints concerned. In order to ensure the robustness of the system, nonlinear disturbance observers are introduced to estimate the uncertainty of the system model. Finally, the stability of the integrated design method is proven based on the Lyapunov theory. Simulation results verify the effectiveness of the integrated guidance and control design method proposed in this paper in multimissile angle penetration attack.